2014
DOI: 10.1016/j.tsf.2013.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Direct current magnetron sputtered ZrB2 thin films on 4H-SiC(0001) and Si(100)

Abstract: ZrB2 thin films have been synthesized using direct current magnetron sputtering from a ZrB2 compound target onto 4H-SiC(0001) and Si (100)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…In contrast, we [14] and others [9,10,18] have shown that it is possible to grow crystalline films also at temperatures below 200 °C. Characteristic for these studies are a short target-to-substrate distance (5.5 cm or 7 cm) and high sputtering powers applied to the targets ranging from 2.8 Wcm -2 to 11.32 Wcm -2 .…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…In contrast, we [14] and others [9,10,18] have shown that it is possible to grow crystalline films also at temperatures below 200 °C. Characteristic for these studies are a short target-to-substrate distance (5.5 cm or 7 cm) and high sputtering powers applied to the targets ranging from 2.8 Wcm -2 to 11.32 Wcm -2 .…”
Section: Introductionmentioning
confidence: 58%
“…ZrB2 thin films can be synthesized by sputtering from a compound or composite target [7][8][9][10][11][12][13][14][15]. This is the predominant synthesis route, given the lack of a suitable boron precursor for reactive sputtering.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations